2021
DOI: 10.3389/fbioe.2020.624096
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Musculoskeletal Pathologies and Regeneration

Abstract: The incidence of musculoskeletal diseases is steadily increasing with aging of the population. In the past years, extracellular vesicles (EVs) have gained attention in musculoskeletal research. EVs have been associated with various musculoskeletal pathologies as well as suggested as treatment option. EVs play a pivotal role in communication between cells and their environment. Thereby, the EV cargo is highly dependent on their cellular origin. In this review, we summarize putative mechanisms by which EVs can c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 286 publications
0
24
0
1
Order By: Relevance
“…The authors isolated EVs from osteoblasts of patients with hip OA(coxarthrosis/CA), osteoporosis (OP), or a combination of both (CA/OP) and demonstrated that the viability and differentiation potential of bone marrow-MSCs stimulated in vitro with EVs released by osteoblasts from CA, OP, and CA/OP patients was significantly reduced compared to control groups, suggesting that pathological EVs exerted catabolic effects that should be taken into consideration when harnessing them as therapeutic drugs [62]. EVs secreted by osteocytes have been isolated from the blood, indicating that circulating EVs could represent interesting biomarkers to be investigated, being able to transfer their cargo to distant recipient cells and regulating several biological responses in musculoskeletal disorders [63,64].…”
Section: Evs As Therapeutic Tools In Pre-clinical Studiesmentioning
confidence: 99%
“…The authors isolated EVs from osteoblasts of patients with hip OA(coxarthrosis/CA), osteoporosis (OP), or a combination of both (CA/OP) and demonstrated that the viability and differentiation potential of bone marrow-MSCs stimulated in vitro with EVs released by osteoblasts from CA, OP, and CA/OP patients was significantly reduced compared to control groups, suggesting that pathological EVs exerted catabolic effects that should be taken into consideration when harnessing them as therapeutic drugs [62]. EVs secreted by osteocytes have been isolated from the blood, indicating that circulating EVs could represent interesting biomarkers to be investigated, being able to transfer their cargo to distant recipient cells and regulating several biological responses in musculoskeletal disorders [63,64].…”
Section: Evs As Therapeutic Tools In Pre-clinical Studiesmentioning
confidence: 99%
“…The use of exosomes in treating OA has been previously reviewed [195]. An intraarticular injection of exosomes to the side of the knee injury is favorable because of its ability to increase exosome accumulation at the target tissues and simultaneously reduce unnecessary systemic exposure.…”
Section: Direct Needle Injection: Exosome Gel and Formulationmentioning
confidence: 99%
“…iPSCs, iPSC-derived MSCs, and iPSC-derived MSC-like mesenchymal progenitor cells could also be alternative inexhaustible EV production sources due to their unlimited proliferative potential. 168 , 169 In addition, there is no standard protocol for ensuring exosome or EV quality.…”
Section: Conclusion and Perspectivementioning
confidence: 99%